Manufacturing method of water-absorbent resin

By using water-soluble polyamide glycoside as an improved agent in the production process of water-absorbing resin, the problems of slow absorption speed and liquid reflux are solved, and efficient liquid absorption and flowability are achieved, while avoiding dust problems.

JP7671339B2Active Publication Date: 2025-05-01NIPPON SHOKUBAI CO LTD
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
JP2023507181
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-20
Filing Date
2022-03-17
Publication Date
2025-05-01
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Traditional water-absorbing resins absorb slowly when absorbing liquids and are prone to liquid reflux problems, and adding liquid permeability improvers will lead to dust problems.

Method used

By adding water-soluble polyalkylene glycol as an improvement agent in the production process of the water-absorbing resin, the absorption rate of the resin under initial pressure is improved without the need to add a large amount of liquid perseverance improver.

Benefits of technology

It is achieved to improve the initial absorption rate and liquid fluidity of the water-absorbing resin without increasing the liquid permeability modification agent, and reduce dust problems and liquid reflux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671339000001
    Figure 0007671339000001
Patent Text Reader

Abstract

As a method for producing a water absorbent resin, which has an excellent initial water absorption rate under pressure, substantially without the addition of a liquid permeability improver, the present invention provides a method that comprises a step in which a monomer is polymerized, while adding a specific polyalkylene glycol thereto, so as to produce a hydrous gel-like crosslinked polymer that internally contains the polyalkylene glycol of a specific molecular weight during or after the polymerization. With respect to this method, the hydrous gel-like crosslinked polymer is formed to have a free swell capacity within a specific range; and the water absorbent resin as a final product is configured so that various physical properties (CRC, AAP, SFC, FSR) thereof are within prescribed ranges.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a water-absorbent resin. [Background technology]

[0002] Superabsorbent polymers (SAPs) are used as absorbents contained in absorbent articles such as paper diapers, sanitary napkins, so-called incontinence pads, etc. Generally, surface-crosslinked water-absorbent resins are used as the SAPs.

[0003] In the above-mentioned applications, the water-absorbent resin absorbs and swells with aqueous liquids such as urine, thereby sealing in the aqueous liquid. Therefore, the water-absorbent resin needs to have a high absorption capacity for the aqueous liquid and to rapidly absorb the aqueous liquid, and is required to have a high water-absorption rate. One physical property that indicates the water-absorption rate of the water-absorbent resin is the FSR (free swelling rate).

[0004] Furthermore, in addition to having a high absorption capacity and a high water absorption rate, the water-absorbent resin is required to have good liquid permeability. If the liquid permeability is low, the discharged liquid cannot reach the inside of the absorbent article, but remains on the surface side and may leak from the absorbent article. One physical property that indicates the liquid permeability is SFC (saline flow conductivity).

[0005] Patent documents 7 to 12 disclose water-absorbent resins with improved T20 (time to achieve absorption of 20 g / g) as the initial water-absorption rate under pressure. As a method for improving the T20 of a water-absorbent resin, Patent document 8 describes foaming polymerization, and Patent documents 9 to 12 describe gel pulverization using specific pulverization conditions.

[0006] Patent Documents 14 and 15 disclose a technique known as wet grinding, in which the die diameter of a gel grinder is reduced to apply a strong shear force to the gel during gel grinding in order to improve the FSR of a water-absorbent resin.

[0007] Patent Document 1 discloses a technique for reducing fusion of crushed gel by adding a substance that inhibits fusion between gels, such as a surfactant, during polymerization of a water-absorbent resin or gel crushing. Patent Document 4 discloses the use of polyethylene glycol (PEG) as a release agent during gel crushing.

[0008] Patent Document 3 describes that the water-absorbing resin contains a compound derived from polyalkylene glycol and a polyvalent metal salt, and Patent Document 5 describes that a water-soluble polymer is added to the water-absorbing resin in order to improve the water absorption rate. Patent Document 2 discloses that PEG is added to the water-absorbing resin to suppress the initial coloring of the water-absorbing resin. Patent Document 6 describes that only a polyhydric alcohol such as PEG is used as an internal crosslinking agent, and Patent Document 13 describes that PEG is used as a thickening agent in foaming polymerization. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2016 / 204302 Brochure [Patent Document 2] International Publication No. 2008 / 096713 Brochure [Patent Document 3] International Publication No. 2009 / 075204 Brochure [Patent Document 4] Japanese Patent Publication "JP Patent Publication No. 2001-342258" [Patent Document 5] Japanese Patent Publication No. 57-167307 [Patent Document 6] Japanese Patent Publication No. 55-84304 [Patent Document 7] Japanese Patent Publication No. 2014-515987 [Patent Document 8] International Publication No. 2010 / 095427 Brochure [Patent Document 9] International Publication No. 2017 / 164452 Brochure [Patent Document 10] International Publication No. 2018 / 117391 Brochure [Patent Document 11] International Publication No. 2018 / 139768 Brochure [Patent Document 12] International Publication No. 2016 / 085123 Brochure [Patent Document 13] International Publication No. 2016 / 204390 Brochure [Patent Document 14] International Publication No. 2016 / 126079 Brochure [Patent Document 15] International Publication No. 2016 / 158975 Brochure Summary of the Invention [Problem to be solved by the invention]

[0010] However, absorbent articles such as disposable diapers made using the conventional water-absorbing resins still have the problem that the absorption of aqueous liquids is slow and the aqueous liquids bleed (backflow). As an approach from the viewpoint of water-absorbing resins to solve such problems, it has been found that it is necessary to improve the initial water absorption speed under pressure. That is, when an absorbent article comes into contact with an aqueous liquid, a water-absorbing resin that quickly diffuses and absorbs the aqueous liquid in the initial stage is required.

[0011] Furthermore, the addition of a liquid permeability improver to the water absorbent resin may cause dust problems such as powdering and filter clogging in the production line of the water absorbent resin and the disposable diaper, etc. Therefore, it is required to improve the initial water absorption rate under pressure without substantially adding a liquid permeability improver to the water absorbent resin.

[0012] An object of the present invention is to provide a method for producing a water-absorbent resin which is excellent in initial water absorption rate under pressure even without substantially adding a liquid-permeability improving agent. [Means for solving the problem]

[0013] In order to solve the above problems, a method for producing a water-absorbent resin according to one aspect of the present invention is as follows. (i) preparing an aqueous solution of a (meth)acrylic acid (salt)-based monomer; (ii) polymerizing the aqueous (meth)acrylic acid (salt) monomer solution; (iii) a step of gel-pulverizing the hydrogel crosslinked polymer produced during or after the polymerization to obtain a particulate hydrogel; (iv) drying the particulate hydrogel to obtain a dry polymer; (v) pulverizing and / or classifying the dried polymer to obtain a particulate water absorbent resin before surface crosslinking; (vi) surface cross-linking the particulate water absorbent resin before surface cross-linking; A method for producing a surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin, comprising: In the step (i) and / or (ii), a water-soluble polyalkylene glycol having a weight average molecular weight of 2000 or less is added, and the total amount of the water-soluble polyalkylene glycol added in the step (i) and / or (ii) is 0.01% by mass to 1% by mass with respect to the total mass of the monomers contained in the aqueous monomer solution; The water absorption capacity of the hydrogel crosslinked polymer without load is 31 g / g or less and 20 g / g or more, A method for producing a water-absorbent resin, wherein the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water-absorbent resin obtained by the above-mentioned production method satisfies the following (1) to (4): (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less (2) Absorption capacity under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (× 10 -7 cm 3 ·sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g s) or more Preferably, in the method for producing a water-absorbent resin according to one aspect of the present invention, the polyalkylene glycol has a weight average molecular weight of 200 or more.

[0014] Preferably, in the method for producing a water absorbent resin according to one aspect of the present invention, the content ratio of the polyalkylene glycol to the entire surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is adjusted to be 0.01 mass % to 1 mass %.

[0015] Preferably, in the method for producing a water absorbent resin according to one aspect of the present invention, the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is an irregularly pulverized surface-crosslinked water absorbent resin.

[0016] Preferably, in the method for producing a water-absorbent resin according to one aspect of the present invention, the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water-absorbent resin has a water content of 5 mass % or less.

[0017] Preferably, in the method for producing a water-absorbent resin according to one aspect of the present invention, the particulate hydrogel obtained by gel-crushing the hydrogel-like crosslinked polymer in the step (iii) has a logarithmic standard deviation (σ) showing a particle size distribution of 0.2 to 1.5. Effect of the Invention

[0018] The method for producing a water-absorbent resin according to one aspect of the present invention provides a water-absorbent resin having an excellent initial water absorption rate under pressure (T20) even without substantially adding a liquid-permeability enhancer. Therefore, for example, when an absorbent article such as a paper diaper is composed of a water-absorbent resin produced by the production method according to the present invention, the water-absorbent resin has excellent liquid permeability of a swollen gel, absorbs aqueous liquids quickly, and suppresses bleeding (backflow) of the aqueous liquid. Since a liquid-permeability enhancer is not substantially added, dust problems such as powdering and clogging of filters in the production line of the water-absorbent resin and the paper diaper are suppressed, and further, an absorbent article that is safer for consumers can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to this, and various modifications are possible within the described range, and the embodiments and examples obtained by appropriately combining the technical means described in the different embodiments and examples are also included in the technical scope of the present invention. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less". In addition, "(meth)acrylic" means "acrylic and / or methacrylic". Furthermore, the mass of the water-absorbing resin, etc., represents a numerical value converted into a solid content unless otherwise specified.

[0020] [1] Definitions (1-1) Water-absorbing resin In this specification, the term "water-absorbent resin" refers to a water-swellable, water-insoluble crosslinked polymer. Here, "water-swellable" means that the absorption capacity without load (also called centrifuge retention capacity (CRC)) specified in NWSP 241.0.R2(15) is 5 g / g or more, and "water-insoluble" means that the soluble content (Ext) specified in NWSP 270.0.R2(15) is 50 mass% or less.

[0021] The water-absorbent resin is preferably a hydrophilic cross-linked polymer obtained by cross-linking polymerization of a (meth)acrylic acid (salt) monomer. However, the total amount, i.e., 100% by mass, does not need to be the hydrophilic cross-linked polymer, and additives and the like can be contained within a range that satisfies the required performance such as the CRC and Ext.

[0022] In addition, in this specification, the water absorbent resin may refer to "a polymer crosslinked only inside, that is, a polymer in which the crosslink density of the inside and the surface is substantially the same" or "a polymer crosslinked between the inside and the surface, that is, a polymer in which the crosslink density of the surface is relatively high compared to the crosslink density of the inside". In this specification, the "polymer crosslinked only inside" and the "polymer crosslinked between the inside and the surface" are not distinguished in principle, and both are expressed as "water absorbent resin". However, when it is necessary to clearly distinguish the presence or absence of surface crosslinking, the "polymer crosslinked only inside" is expressed as "water absorbent resin before surface crosslinking" or "base polymer" since it is before surface crosslinking is performed, and the "polymer crosslinked between the inside and the surface, that is, a polymer in which the crosslink density of the surface is relatively high compared to the crosslink density of the inside" is expressed as "water absorbent resin after surface crosslinking" or "surface crosslinked water absorbent resin". In addition, "before surface crosslinking" means "before adding a surface crosslinking agent" or "before the surface crosslinking reaction by heat treatment begins even after the surface crosslinking agent is added".

[0023] The term "water-absorbing resin" may refer to only the resin component, or may include components other than the resin, such as additives.

[0024] (1-2) "NWSP" "NWSP" is an abbreviation for Non-Woven Standard Procedures-Edition 2015, which is a standardized method for evaluating nonwoven fabrics and their products in Europe and the United States, jointly issued by EDANA (European Disposables and Nonwovens Associations) and INDA (Association of the Nonwoven Fabrics Industry). The NWSP also shows a standard measurement method for water-absorbent resins. In this specification, the physical properties of the water-absorbent resin are measured in accordance with the original NWSP (2015). In this specification, unless otherwise specified, the measurement methods for various physical properties of the water-absorbent resin follow the measurement methods in the following examples.

[0025] [2] Water-absorbing resin A water absorbent resin produced by a production method according to one embodiment of the present invention is a particulate poly(meth)acrylic acid (salt)-based water absorbent resin, in which a water-soluble polyalkylene glycol having a weight-average molecular weight of 2000 or less is present internally, the water absorbent resin is substantially free of a liquid permeability improver, and satisfies the following (1) to (5). (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less (2) Absorption capacity under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (× 10 -7 cm 3 ·sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g s) or more (5) Initial water absorption rate under pressure (T20) is 145 seconds or less The present inventors have conducted extensive research to solve the above problems, and have found that a water-absorbent resin having an improved initial water absorption rate under pressure (T20) can be obtained without substantially adding a liquid permeability improver by incorporating a water-soluble polyalkylene glycol having a specific molecular weight into the water-absorbent resin, and have completed the present invention. The initial water absorption rate under pressure (T20, etc.) affects the liquid absorption or Re-Wet of an absorbent article. For example, when an absorbent article such as a paper diaper is configured to include a water-absorbent resin having a high initial water absorption rate under pressure (T20, etc.), the absorbent article quickly absorbs discharged liquids such as urine, and the bleeding (return) of the discharged liquid is also suppressed. In addition, since no liquid permeability improver is added, dust problems such as powdering and clogging of filters in the production line of the water-absorbent resin and the paper diaper are suppressed.

[0026] [2-1] Poly(meth)acrylic acid (salt)-based water-absorbent resin In one embodiment of the present invention, the term "poly(meth)acrylic acid (salt)-based water absorbent resin" refers to a hydrophilic crosslinked polymer obtained by crosslinking and polymerizing a monomer composition containing a (meth)acrylic acid (salt)-based monomer.

[0027] In this specification, "(meth)acrylic acid (salt)" means (meth)acrylic acid and / or a salt thereof, and "a monomer composition containing a (meth)acrylic acid (salt)-based monomer" means a monomer composition containing 50 mol % or more of (meth)acrylic acid (salt) based on the total monomers excluding a crosslinking agent.

[0028] In other words, the poly(meth)acrylic acid (salt)-based water absorbent resin is a crosslinked polymer containing 50 mol % or more of structural units derived from (meth)acrylic acid (salt) relative to the total structural units constituting the poly(meth)acrylic acid (salt)-based water absorbent resin, and is a crosslinked polymer having a graft component as an optional component.

[0029] The poly(meth)acrylic acid (salt)-based water absorbent resin is a crosslinked polymer obtained by using, as a raw material, 50 mol % or more, preferably 70 mol % or more, more preferably 90 mol % or more, and preferably 100 mol % or less, more preferably substantially 100 mol % of (meth)acrylic acid (salt), based on the portion excluding the internal crosslinking agent among the monomers involved in the polymerization reaction.

[0030] The shape of the water-absorbent resin produced by the production method according to one embodiment of the present invention is particulate. The particulate water-absorbent resin may be, for example, irregularly crushed (irregular), spherical, fibrous, rod-like, approximately spherical, or flat. Among these, it is preferable that at least a part of the water-absorbent resin is irregularly crushed. In consideration of use in absorbent articles such as baby diapers, it is more preferable that the water-absorbent resin is irregular among the above-mentioned particle shapes in terms of the diffusibility of liquid (urine) and the difficulty of falling off from pulp. The particulate water-absorbent resin is referred to as particulate water-absorbent resin whether it is a single particle or an aggregate of multiple particles. "Particulate" means having a particle form, and a particle means a solid or liquid granular small body having a measurable size (JIS Industrial Terminology Dictionary, 4th Edition, p. 2002).

[0031] <Monomer> "Monomer" refers to a raw material component (monomer) forming a water-absorbent resin (polymer), and includes a (meth)acrylic acid (salt)-based monomer as the main component, as well as a monomer other than the (meth)acrylic acid (salt)-based monomer and an internal crosslinking agent. In other words, the entire monomer forming the water-absorbent resin is a monomer composition. The (meth)acrylic acid (salt)-based monomer includes (meth)acrylic acid and its salt.

[0032] As the monomer other than the (meth)acrylic acid (salt) monomer, among the monomers having an unsaturated double bond (ethylenically unsaturated monomers), a monomer containing an acid group is preferable.Specific examples of the monomer include anionic unsaturated monomers such as (anhydrous) maleic acid, fumaric acid, crotonic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate, and / or salts thereof.These monomers are used alone or in combination as required.

[0033] Examples of the salt include alkali metal salts, ammonium salts, and amine salts, with sodium salts, potassium salts, lithium salts, and ammonium salts being more preferred, and sodium salts being particularly preferred.

[0034] In addition, the monomer composition containing a (meth)acrylic acid (salt)-based monomer is preferably neutralized in the range of 10 to 90 mol %, more preferably neutralized in the range of 40 to 80 mol %, and particularly preferably neutralized in the range of 60 to 75 mol %.

[0035] Therefore, the monomer composition containing a (meth)acrylic acid (salt)-based monomer is preferably neutralized with a neutralizing liquid containing a basic compound such as an alkali metal hydroxide, such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, a carbonate (hydrogen) salt, such as sodium carbonate (hydrogen) or potassium carbonate (hydrogen), or ammonia, and is particularly preferably neutralized with a neutralizing liquid containing sodium hydroxide.

[0036] In addition, the monomer composition may contain, as necessary, a "hydrophilic or hydrophobic unsaturated monomer (hereinafter referred to as "other monomer")" in addition to the above-mentioned "(meth)acrylic acid (salt)-based monomer" and "monomer other than (meth)acrylic acid (salt)-based monomer". Examples of the other monomer include mercaptan group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; amide group-containing unsaturated monomers such as N-vinyl-2-pyrrolidone, N-vinylacetamide, (meth)acrylamide, N-isopropyl(meth)acrylamide, N-ethyl(meth)acrylamide, and N,N-dimethyl(meth)acrylamide; and amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, and N,N-dimethylaminopropyl(meth)acrylamide. The amount of the other monomers used may be such that the physical properties of the obtained water absorbent resin are not impaired, and specifically, the amount is 50 mol % or less, more preferably 20 mol % or less, based on the part of the monomer composition excluding the internal crosslinking agent.

[0037] <Internal crosslinking agent> The water-absorbent resin is internally crosslinked with an internal crosslinking agent.

[0038] Examples of the internal crosslinking agent include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerin, pentaerythritol, ethylenediamine, polyethyleneimine, and glycidyl (meth)acrylate. At least one type of internal crosslinking agent is selected from these internal crosslinking agents, taking into consideration reactivity and the like.

[0039] In the present invention, from the viewpoint of the water absorption performance of the water absorbent resin, an internal crosslinking agent having two or more polymerizable unsaturated groups is preferably selected, and an internal crosslinking agent having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structure is more preferably selected. Specific examples of the polymerizable unsaturated groups include allyl groups and (meth)acrylate groups. Among them, (meth)acrylate groups are preferred. In addition, an example of the internal crosslinking agent having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structure is polyethylene glycol di(meth)acrylate. The number of alkylene glycol units (hereinafter referred to as "n") is preferably 1 or more, more preferably 2 or more, even more preferably 4 or more, and particularly preferably 6 or more, and is preferably 100 or less, more preferably 50 or less, even more preferably 20 or less, and particularly preferably 10 or less.

[0040] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more, more preferably 0.001 mol% or more, and even more preferably 0.01 mol% or more, and is preferably 10 mol% or less, more preferably 5 mol% or less, and even more preferably 1 mol% or less, based on the monomer composition excluding the internal crosslinking agent. By using an amount within this range, a water-absorbing resin having a desired water-absorbing performance can be obtained. On the other hand, if the amount used is outside this range, the gel strength may decrease, and the water-soluble content may increase, or the absorption capacity may decrease.

[0041] <Surface cross-linking agent> The water-absorbent resin produced by the production method according to one embodiment of the present invention is surface-crosslinked. Examples of the surface-crosslinking agent used include the surface-crosslinking agents described in U.S. Pat. No. 7,183,456. At least one type of surface-crosslinking agent is selected from these surface-crosslinking agents in consideration of reactivity and the like. In addition, from the viewpoint of the handling of the surface-crosslinking agent and the water-absorbing performance of the water-absorbent resin, a surface-crosslinking agent having two or more functional groups that react with a carboxyl group and an organic compound that forms a covalent bond is preferably selected.

[0042] Specific examples of the surface cross-linking agent include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, and 2,5-pentanediol. Polyhydric alcohol compounds such as hexanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,3-hexanediol, 2,4-hexanediol, glycerin, polyglycerin, diethanolamine, and triethanolamine; polyhydric amine compounds such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine, and polyethyleneimine; haloepoxy compounds, polyhydric amines, and polyamines. Condensates of epoxy compounds with haloepoxy compounds; oxazoline compounds such as 1,2-ethylenebisoxazoline; oxazolidinone compounds; 1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one, 4, Examples of the alkylene carbonate compounds include 6-dimethyl-1,3-dioxan-2-one and 1,3-dioxopan-2-one; polyglycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and glycidol; oxetane compounds; vinyl ether compounds; and cyclic urea compounds.These may be used alone or in combination of two or more.

[0043] The water absorbent resin produced by the production method according to one embodiment of the present invention more preferably contains a surface-crosslinked, irregularly crushed water absorbent resin. This is preferable because it can achieve both water absorption performance under pressure and the resistance to falling off from the pulp. In particular, the water absorbent resin produced by the production method according to one embodiment of the present invention contains the surface-crosslinked, irregularly crushed water absorbent resin in an amount of preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, based on the entire water absorbent resin.

[0044] [2-2] Polyalkylene glycol The water-absorbing resin produced by the production method according to one embodiment of the present invention contains a water-soluble polyalkylene glycol having a weight-average molecular weight of 2000 or less. Here, the polyalkylene glycol being contained in the water-absorbing resin means that the polyalkylene glycol is present inside the water-absorbing resin. It is sufficient that most of the polyalkylene glycol is present inside the water-absorbing resin, and a part of the polyalkylene glycol may be present on the surface of the water-absorbing resin. In other words, it is sufficient that the polyalkylene glycol is not present only near the surface, and as long as this is the case, a part of the polyalkylene glycol may be present on the surface.

[0045] The polyalkylene glycol may be one having a structure represented by the following general formula (1).

[0046] H-(OR) n -OH (1) In the general formula (1), R is an alkylene group having 2 to 4 carbon atoms, which may be linear or branched, and n has an average value of 4 to 50, and more preferably 6 to 15.

[0047] In the general formula (1), the oxyalkylene groups (-OR-) in one molecule may be the same or may contain two or more kinds of oxyalkylene groups. More specifically, the polyalkylene glycol may be, for example, polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, polyethylene glycol-polypropylene glycol-polybutylene glycol copolymer, etc. These polyalkylene glycols may be used alone or in combination of two or more kinds.

[0048] In one embodiment of the present invention, the polyalkylene glycol is water-soluble. Here, in the present invention, "water-soluble" means that it dissolves in an amount of 5 g or more, more preferably 10 g or more, in 100 g of water at 25° C. Since the polyalkylene glycol is water-soluble, it can be dissolved in an aqueous monomer solution, and therefore the polyalkylene glycol can be suitably contained in the water absorbent resin.

[0049] The weight average molecular weight of the polyalkylene glycol used in one embodiment of the present invention is 2000 or less. The weight average molecular weight of the polyalkylene glycol is 2000 or less, so that the water-absorbing resin in which it is contained can improve the initial water absorption rate under pressure. The weight average molecular weight of the polyalkylene glycol is preferably 200 or more, more preferably 300 or more, and even more preferably 400 or more. The weight average molecular weight is more preferably 1500 or less, and more preferably 1000 or less. Here, the weight average molecular weight of the polyalkylene glycol is a value measured by gel permeation chromatography.

[0050] The content of the polyalkylene glycol contained in the water absorbent resin is preferably 0.01% by mass to 1% by mass with respect to the entire water absorbent resin. When the content of the polyalkylene glycol is 0.01% by mass to 1% by mass, the water absorbent resin is excellent in the initial water absorption rate under pressure (T20, etc.). The content of the polyalkylene glycol is more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, even more preferably 0.15% by mass or more, and even more preferably 0.20% by mass or more. In addition, the content of the polyalkylene glycol is more preferably 0.80% by mass or less, even more preferably 0.60% by mass or less, and particularly preferably 0.40% by mass or less.

[0051] The content ratio of the polyalkylene glycol present in the water absorbent resin can be quantified by extracting water-soluble components from the water absorbent resin and analyzing the extract by liquid chromatography. The extraction method is not particularly limited, and a conventionally known method may be appropriately selected. The presence of the polyalkylene glycol in the water absorbent resin can be proved by analyzing the content of polyalkylene glycol in each classified particle size range of the water absorbent resin, and the content of polyalkylene glycol is uniform and has no particle size dependency. This is based on the fact that if polyalkylene glycol is present on the surface of the water absorbent resin, the content of polyalkylene glycol in the water absorbent resin of the small particle size range will be larger than the content of polyalkylene glycol in the water absorbent resin of the large particle size range, while when polyalkylene glycol is present in the water absorbent resin, the content of polyalkylene glycol is uniform regardless of particle size.

[0052] [2-3] Liquid permeability improver The water absorbent resin produced by the production method according to one embodiment of the present invention does not substantially contain a liquid permeability improver. Here, "substantially does not contain" means that the liquid permeability improver is not contained, or even if the liquid permeability improver is contained, the content ratio is less than 0.1 mass% (preferably less than 0.001 mass%) with respect to the whole water absorbent resin. When the liquid permeability improver is contained in an amount of 0.1 mass% or more, the physical properties such as the absorption capacity and water absorption speed of the water absorbent resin tend to decrease. In one embodiment of the present invention, the initial water absorption speed under pressure (T20, etc.) of the water absorbent resin can be improved without adding a liquid permeability improver. And, dust problems such as powdering and clogging of filters in the production line of the water absorbent resin and the production line of the paper diaper are suppressed.

[0053] The liquid permeability improver is a spacer (support) that maintains the gap between particles of the water-absorbent resin even under pressure, and examples of the liquid permeability improver include a cationic polymer-containing liquid permeability improver and an inorganic substance-containing liquid permeability improver. Examples of the inorganic substance-containing liquid permeability improver include a polyvalent metal salt and a water-insoluble inorganic particle. The polyvalent metal salt contains a divalent or higher, preferably a trivalent or higher, metal cation. Examples of trivalent or higher metal cations include aluminum, zirconium, and titanium. Examples of the polyvalent metal salt include inorganic salts of polyvalent metals such as aluminum sulfate, aluminum chloride, zirconium oxide chloride, ammonium zirconium carbonate, potassium zirconium carbonate, potassium zirconium carbonate, zirconium sulfate, hydroxyl chloride, and zirconium nitrate, and polyvalent metal compounds such as organic salts of polyvalent metals such as aluminum acetate, aluminum lactate, zirconium acetate, titanium triethanolamine, and titanium lactate.

[0054] Examples of the water-insoluble inorganic fine particles include silicon dioxide, titanium dioxide, aluminum oxide, magnesium oxide, zinc oxide, talc, metal phosphates (e.g., calcium phosphate, barium phosphate, and aluminum phosphate), metal borates (e.g., titanium borate, aluminum borate, iron borate, magnesium borate, manganese borate, and calcium borate), silicic acid or its salts, water-insoluble fine inorganic powders such as clay, diatomaceous earth, zeolite, bentonite, kaolin, hydrotalcite, and activated clay, and organic fine powders such as calcium lactate, aluminum lactate, and metal soaps (polyvalent metal salts of long-chain fatty acids). The inorganic fine particles usually have a volume average particle diameter of 10 μm or less. In this embodiment, a water-absorbent resin having an improved initial water absorption rate under pressure (T20, etc.) can be obtained without substantially adding these polyvalent metal salts and water-insoluble inorganic particles.

[0055] [2-4] Properties of water-absorbent resin The water absorbent resin produced by the production method according to one embodiment of the present invention has a non-loaded absorption capacity (CRC) of preferably 20 g / g or more, more preferably 25 g / g or more, even more preferably 28 g / g or more, and particularly preferably 29 g / g or more. The higher the upper limit of the CRC, the better, but in terms of the balance with other physical properties, it is preferably 35 g / g or less, more preferably 32 g / g, even more preferably 31 g / g or less, and particularly preferably 30 g / g or less.

[0056] The absorbency under pressure (AAP) of the water absorbent resin produced by the production method according to one embodiment of the present invention at a pressure of 0.7 psi is preferably 25 g / g or more, more preferably 25.2 g / g or more, even more preferably 25.4 g / g or more, particularly preferably 25.6 g / g or more, and most preferably 25.8 g / g or more. The upper limit is not particularly limited, but is preferably 30 g / g or less from the viewpoint of balance with other physical properties.

[0057] When the AAP is 25 g / g or more, the amount of liquid returning when pressure is applied to the absorbent (usually called "Re-Wet") is not too large, so it is suitable for use as an absorbent for absorbent articles such as disposable diapers. The AAP can be controlled by particle size, surface cross-linking agents, etc.

[0058] The saline flow conductivity (SFC) of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 15×10 -7 cm 3 sec / g or more, and more preferably 18×10 -7 cm 3 sec / g or more, and more preferably 20×10 -7 cm 3 sec / g or more, and particularly preferably 30×10 -7 cm 3 ·sec / g or more. The upper limit of the SFC is not particularly limited, and a higher value is preferable.

[0059] The free swelling rate (FSR) of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 0.33 g / (g·s) or more, more preferably 0.36 g / (g·s) or more, further preferably 0.39 g / (g·s) or more, and particularly preferably 0.42 g / (g·s) or more. The FSR is related to the surface area and irregularly crushed particle shape of the water absorbent resin, and it is assumed that the higher the FSR, the higher the surface area of ​​the water absorbent resin and / or the more irregularly crushed the particle shape of the water absorbent resin (the shape farther away from a spherical shape).

[0060] The initial water absorption rate under pressure (T20) of the water absorbent resin produced by the production method according to one embodiment of the present invention may be 145 seconds or less. T20 is preferably 140 seconds or less, more preferably 135 seconds or less, further preferably 130 seconds or less, 120 seconds or less, 110 seconds or less, or 100 seconds or less. By setting T20 within the above range, for example, when the water absorbent resin is contained in an absorbent article such as a paper diaper, the absorption of discharged liquid such as urine is accelerated and bleeding (backflow) of the discharged liquid is also suppressed.

[0061] In a manufacturing method according to one embodiment of the present invention, a monomer is polymerized to produce a water-absorbent resin having a specific polyalkylene glycol therein during or after polymerization, and the water-absorbent gel crosslinked polymer is made to have a water absorption capacity without pressure within a predetermined range, and the various physical properties (CRC, AAP, SFC, FSR) of the resin are set within a specified range for the finally obtained water-absorbent resin, thereby producing a water-absorbent resin having a small T20 value and excellent initial water absorption rate under pressure. In other words, a water-absorbent resin obtained by the manufacturing method and having various physical properties of the resin within the above-mentioned range has a small T20 value and excellent initial water absorption rate under pressure. The various physical properties can be controlled by the particle size, particle shape, surface crosslinking, etc. of the water-absorbent resin.

[0062] When the various physical properties (CRC, AAP, SFC, FSR) of the water absorbent resin are within the specified range, the T20 value becomes small and the initial water absorption rate under pressure increases. It is not clear why this happens. Among these physical properties, AAP(0.7) / SFC * is preferably 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, or 0.7 or more, and more preferably 5.0 or less, 4.0 or less, 3.0 or less, 2.0 or less, 1.5 or less, or 1.3 or less. * =SFC / (1×10 -7 ).

[0063] The initial water absorption rate under pressure (T15) of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 90 seconds or less. T15 is more preferably 80 seconds or less, more preferably 75 seconds or less, and even more preferably 70 seconds or less. By setting T15 within the above range, for example, when the water absorbent resin is contained in an absorbent article such as a disposable diaper, the absorption of discharged liquid such as urine is quick and bleeding (backflow) of the discharged liquid is also suppressed.

[0064] The initial water absorption rate under pressure (T10) of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 50 seconds or less. T10 is more preferably 46 seconds or less, more preferably 43 seconds or less, and even more preferably 40 seconds or less. By setting T10 within the above range, for example, when an absorbent article such as a disposable diaper is formed containing the water absorbent resin, the absorbency of discharged liquid such as urine is quick and bleeding (backflow) of the discharged liquid is suppressed.

[0065] The initial water absorption speed under pressure (T5) of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 25 seconds or less. T5 is more preferably 22 seconds or less, more preferably 21 seconds or less, and even more preferably 19 seconds or less. By setting T5 within the above range, for example, when an absorbent article such as a disposable diaper is formed containing the water absorbent resin, the absorbency of discharged liquid such as urine is quick and bleeding (backflow) of the discharged liquid is suppressed.

[0066] The total (T5+T10+T15) of the initial water absorption speeds under pressure T5, T10 and T15 of the water absorbent resin produced by the production method according to one embodiment of the present invention is preferably 160 seconds or less, more preferably 140 seconds or less, even more preferably 135 seconds or less, and particularly preferably 130 seconds or less. By setting T5+T10+T15 within the above range, for example, when an absorbent article such as a paper diaper is formed containing the water absorbent resin, the absorbency of discharged liquid such as urine is quick and bleeding (backflow) of the discharged liquid is suppressed.

[0067] The water content of the water absorbent resin produced by the production method according to one embodiment of the present invention is, for example, 15% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, particularly preferably 1% by mass or less, and substantially 0% by mass. The water content is controlled, for example, by drying and surface crosslinking to the predetermined water content, and further adding water or drying as necessary. If the water content is 15% by mass or less, coloring is suppressed, and the decrease in the adhesion and absorption capacity of the water absorbent resin can be suppressed. Furthermore, the decrease in the initial water absorption speed under pressure (T20, T5, T10, T15) of the water absorbent resin can be suppressed.

[0068] [3] Manufacturing method of water-absorbent resin A method for producing a water-absorbent resin according to one embodiment of the present invention includes the steps of: (i) preparing an aqueous (meth)acrylic acid (salt)-based monomer solution; (ii) polymerizing the aqueous (meth)acrylic acid (salt)-based monomer solution; (iii) gel-crushing a hydrogel-like crosslinked polymer produced during or after polymerization to obtain a particulate hydrogel; (iv) drying the particulate hydrogel to obtain a dry polymer; (v) pulverizing and / or classifying the dry polymer to obtain a particulate water-absorbent resin before surface-crosslinking; and (vi) surface-crosslinking the particulate water-absorbent resin before surface-crosslinking, to obtain a surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water-absorbent resin. a water-soluble polyalkylene glycol having a weight-average molecular weight of 2000 or less is added in the step (i) and / or (ii), the total amount of the water-soluble polyalkylene glycol added in the step (i) and / or (ii) is 0.01% by mass to 1% by mass with respect to the total mass of the monomers contained in the aqueous monomer solution, the water-containing gel-like crosslinked polymer has a water absorption capacity under no load of 31 g / g or less and 20 g / g or more, and the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin obtained by the above-mentioned production method satisfies the following (1) to (4). (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less (2) Absorption capacity under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (× 10 -7 cm 3 ·sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g s) or more That is, in the method for producing a water-absorbent resin according to one embodiment of the present invention, the water-soluble polyalkylene glycol having a weight-average molecular weight of 2000 or less is added in (i) the step of preparing an aqueous solution of a (meth)acrylic acid (salt)-based monomer, or in (ii) the step of polymerizing the aqueous solution of a (meth)acrylic acid (salt). Alternatively, the polyalkylene glycol may be added in both steps (i) and (ii). This makes it possible to produce a water-absorbent resin containing the polyalkylene glycol.

[0069] The method of adding the polyalkylene glycol is not particularly limited, and the polyalkylene glycol may be added directly to the aqueous monomer solution or to the mixture during polymerization, or may be added in the form of a solution, particularly an aqueous solution.

[0070] Furthermore, the upper limit of the water absorption capacity without pressure of the hydrogel crosslinked polymer formed during or after the polymerization in step (ii) is 31 g / g or less, preferably 30 g / g or less, and the lower limit is 20 g / g or more, preferably 25 g / g or more. By setting the water absorption capacity without pressure of the hydrogel crosslinked polymer containing the polyalkylene glycol within a predetermined range, it is expected that the water absorbent resin produced will have the following form, and as a result, for example, the T20 value of the water absorbent resin is reduced, and the initial water absorption rate of the water absorbent resin under pressure is improved. The method for measuring the water absorption capacity without pressure of the hydrogel crosslinked polymer will be described later.

[0071] In the method for producing a water-absorbent resin according to one embodiment of the present invention, the step (iii) may include a step of confirming that the hydrogel-like crosslinked polymer to be subjected to gel pulverization is a hydrogel-like crosslinked polymer having a water absorption capacity without pressure within the above-mentioned range. As a method for confirming that the water absorption capacity without pressure of the hydrogel-like crosslinked polymer is within the above-mentioned range, for example, a method of dividing a part of the hydrogel-like crosslinked polymer produced during or after the polymerization in the step (ii) and using the part of the hydrogel-like crosslinked polymer as a confirmation sample, measuring the water absorption capacity without pressure for the confirmation sample, and confirming that the measured water absorption capacity without pressure is within the above-mentioned range can be mentioned. After confirming that the value of the water absorption capacity without pressure in the confirmation sample is within the above-mentioned range, the remaining hydrogel-like crosslinked polymer not used for measuring the water absorption capacity without pressure is gel-pulverized to carry out the gel pulverization in the step (iii). However, when steps (i) and (ii) are carried out under conditions that have been confirmed in advance to produce a hydrous gel-like crosslinked polymer having a water absorption capacity without load within the above-mentioned range, the gel pulverization in step (iii) may be carried out without checking the water absorption capacity without load of the confirmation sample.

[0072] (Assumed form) By setting the water absorption capacity without pressure of the hydrogel crosslinked polymer within a predetermined range, the hydrogel crosslinked polymer has a certain degree of high strength. In the hydrogel crosslinked polymer, primary particles aggregate to form secondary aggregates during the gel crushing process. At that time, since the hydrogel crosslinked polymer, which is the primary particle, has high strength and is difficult to deform, and a specific polyalkylene is present inside, it is assumed that the secondary aggregates have many sites where the primary particles are loosely bonded to each other. And, the water-absorbing resin in one embodiment of the present invention obtained by gel crushing the hydrogel crosslinked polymer, drying, crushing and classifying, and surface crosslinking is also assumed to have many sites where the primary particles are loosely bonded to each other, similar to the secondary aggregates. Here, it is considered that the sites where the particles are loosely bonded to each other have voids or, even if voids cannot be confirmed, have a space that can absorb liquids such as water. That is, in the water absorbent resin according to one embodiment of the present invention, although it is not clear whether the sites where the primary particles are loosely bonded to each other act as voids, it is considered that the water absorbent resin according to one embodiment of the present invention has a morphology having many sites where there is a margin for absorbing liquid such as water, and this reduces the T20 value and improves the initial water absorption rate under pressure.

[0073] In addition to the above, it is necessary to set various physical properties (CRC, AAP, SFC, FSR) of the finally obtained water absorbent resin within the specified ranges. This makes it possible to improve the initial water absorption rate under pressure in the produced water absorbent resin, and for example, to reduce the T20 value to a small value of 145 seconds or less.

[0074] The amount of the polyalkylene glycol added is 0.01% by mass to 1% by mass with respect to the total mass of the monomers contained in the aqueous monomer solution. When the amount of the polyalkylene glycol added is 0.01% by mass to 1% by mass, the resulting water absorbent resin is excellent in initial water absorption rate under pressure (T20, etc.). The amount of the polyalkylene glycol added is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, even more preferably 0.15% by mass or more, and particularly preferably 0.20% by mass or more. The amount of the polyalkylene glycol added is preferably 0.80% by mass or less, more preferably 0.60% by mass or less, and even more preferably 0.40% by mass or less. The amount of the polyalkylene glycol added is preferably adjusted so that the content ratio with respect to the entire surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is 0.01% by mass to 1% by mass.

[0075] The poly(meth)acrylic acid (salt)-based water-absorbing resin, the polyalkylene glycol, the liquid permeability enhancer, and the physical properties of the obtained water-absorbing resin are as described in "[2] Water-absorbing resin."

[0076] [3-1] Preparation of (meth)acrylic acid (salt) monomer aqueous solution (step (i)) This step is a step of preparing an aqueous solution of raw materials (monomer composition; in particular, containing a (meth)acrylic acid (salt)-based monomer as a main component and containing at least one type of internal crosslinking agent) that form a water-absorbent resin (polymer). Although a slurry liquid of the monomer composition can also be used, for the sake of convenience, the present specification will explain the aqueous solution of the monomer composition.

[0077] (monomer) The monomers used in this process are raw material components (monomers) forming a water-absorbent resin (polymer) as explained in [Poly(meth)acrylic acid (salt)-based water-absorbent resin], and include a (meth)acrylic acid (salt)-based monomer, a monomer other than the (meth)acrylic acid (salt)-based monomer, and an internal crosslinking agent. In other words, the entire monomers forming the water-absorbent resin are a monomer composition.

[0078] (Neutralization with basic compounds) In the present invention, the (meth)acrylic acid (salt) is preferably partially neutralized with a basic compound as described above. That is, in the present invention, a water-absorbing resin in which the acid group of poly(meth)acrylic acid is partially neutralized is preferred.

[0079] Examples of the basic compound include carbonates and hydrogen carbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, etc. Among them, from the viewpoint of the water absorption performance of the water absorbent resin, a strongly basic compound is selected. In addition, from the viewpoint of handling, the basic compound is preferably in the form of an aqueous solution.

[0080] The neutralization may be carried out before, during, or after polymerization, and may be carried out at multiple times or multiple times. From the viewpoint of production efficiency of the water absorbent resin, it is preferable to carry out the neutralization in a continuous manner.

[0081] In the present invention, the neutralization rate of (meth)acrylic acid (salt) is, as described above, preferably 10 mol% or more, more preferably 40 mol% or more, even more preferably 50 mol% or more, particularly preferably 60 mol% or more, and preferably 90 mol% or less, more preferably 85 mol% or less, even more preferably 80 mol% or less, particularly preferably 75 mol% or less, based on the acid group of the monomer composition. By setting the neutralization rate within this range, it is possible to suppress the deterioration of the water absorption performance of the water absorbent resin. The neutralization rate is applied to any of the neutralization before, during, and after the above-mentioned polymerization. The same is also applied to the water absorbent resin.

[0082] (Internal crosslinking agent) The internal crosslinking agent and the amount used in this step are as described above in the section on [Poly(meth)acrylic acid (salt)-based water-absorbing resin].

[0083] In one embodiment of the present invention, the timing of adding the internal crosslinking agent may be any timing that allows the polymer to be uniformly crosslinked, and may include a method of adding the internal crosslinking agent to an aqueous solution of the monomer composition before polymerization or to a hydrogel during or after polymerization. Among these, a method of adding a predetermined amount of the internal crosslinking agent to an aqueous solution of the monomer composition in advance is preferred.

[0084] (Polyalkylene glycol) In a preferred embodiment of the present invention, the polyalkylene glycol can be added to the aqueous solution of the monomer composition. The polyalkylene glycol may be added in the polymerization step described below. The amount of addition is as described above. Among them, it is preferable to add the polyalkylene glycol in the step of preparing the aqueous solution of the monomer composition.

[0085] (Other substances added to the aqueous solution of the monomer composition) In one embodiment of the present invention, in one or more points of preparing the aqueous solution of the monomer composition, during the polymerization reaction and the crosslinking reaction, or after the polymerization reaction and the crosslinking reaction, from the viewpoint of improving physical properties of a water absorbent resin, the following other substances can be added to the aqueous solution of the monomer composition, the solution during the reaction, or the solution after the reaction.

[0086] Examples of the other substances include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol (PVA), polyacrylic acid (salts), and existing crosslinked products of polyacrylic acid (salts); carbonates, azo compounds, various types of foaming agents that generate bubbles, surfactants, chelating agents, chain transfer agents, and other compounds.

[0087] By using the hydrophilic polymer, a water-absorbing resin grafted with the hydrophilic polymer can be obtained, for example, a polyacrylic acid (salt)-based water-absorbing resin grafted with starch, or a polyacrylic acid (salt)-based water-absorbing resin grafted with PVA can be obtained. These grafted water-absorbing resins are also included in the category of polyacrylic acid (salt)-based water-absorbing resins.

[0088] The amount of the other substances added is adjusted so as not to impair the effects of the present invention. For example, the total amount of the other substances added is preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, particularly preferably 5% by mass or less, and is preferably 0% by mass or more, more preferably more than 0% by mass, based on the aqueous solution of the monomer composition.

[0089] (Monomer component concentration) The monomer composition, polyalkylene glycol, each of the above substances and each component (referred to as "monomer components" in this section) are selected in various ways according to the purpose, and the amounts of each are specified so as to satisfy the above ranges and mixed together to prepare an aqueous solution of the total monomer components (i.e., a mixture of the monomer composition, polyalkylene glycol, each substance and each component). Note that, in one embodiment of the present invention, in addition to preparing an aqueous solution of the total monomer components, it is also possible to prepare a mixed solution of the total monomer components in water and a hydrophilic solvent.

[0090] From the viewpoint of the physical properties of the water-absorbent resin, the total concentration of the monomer components is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less. The total concentration of the monomer components can be determined by adding up the concentrations of the individual monomer components. The concentration of each monomer component is calculated from the following formula (A); Concentration of monomer component (mass%)=[(mass of monomer component) / (mass of aqueous solution including monomer components)]×100 Formula (A) In addition, in the above formula (A), "the mass of the aqueous solution including the total of the monomer components" does not include the mass of the hydrophobic organic solvent in the reversed phase suspension polymerization.

[0091] [3-2] Polymerization step (step (ii)) This step is a step of polymerizing an aqueous monomer solution to obtain a hydrogel-like crosslinked polymer (hereinafter, simply referred to as "aqueous gel"). Preferably, this step is a step of polymerizing an aqueous monomer solution containing a monomer containing acrylic acid (salt) as a main component and at least one type of internal crosslinking agent obtained in the aqueous monomer solution preparation step to obtain a hydrogel.

[0092] (Polymerization initiator) As the polymerization initiator used in one embodiment of the present invention, one or more types can be selected from polymerization initiators used in the production of ordinary water-absorbing resins, depending on the type of monomer to be polymerized, polymerization conditions, etc. Examples of the polymerization initiator include a thermal decomposition initiator and a photodecomposition initiator.

[0093] Examples of the thermally decomposable initiator include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides such as hydrogen peroxide, t-butyl peroxide, and methyl ethyl ketone peroxide; and azo compounds such as azonitrile compounds, azoamidine compounds, cyclic azoamidine compounds, azoamide compounds, alkylazo compounds, 2,2'-azobis(2-amidinopropane)dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride.

[0094] Examples of the photodecomposition initiator include benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, and azo compounds.

[0095] Among these, persulfates are preferred in consideration of cost and ability to reduce residual monomers. In addition, a reducing agent that promotes decomposition of the oxidizing polymerization initiator such as the persulfate or peroxide can be used in combination to form a redox initiator. Examples of the reducing agent include (bis)sulfite (salts) such as sodium sulfite and sodium hydrogensulfite, reducing metals (salts) such as L-ascorbic acid (salts) and ferrous salts, and amines.

[0096] The amount of the polymerization initiator used is preferably 0.001 mol% or more, more preferably 0.010 mol% or more, and preferably 1.000 mol% or less, more preferably 0.500 mol% or less, and even more preferably 0.100 mol% or less, based on the monomers excluding the internal crosslinking agent. The amount of the reducing agent used is preferably 0.0001 mol% or more, more preferably 0.0005 mol% or more, and preferably 0.0200 mol% or less, more preferably 0.0150 mol% or less, based on the monomers excluding the internal crosslinking agent. By using the amount within this range, a water absorbent resin having a desired water absorption performance can be obtained.

[0097] In one embodiment of the present invention, the polymerization reaction may be initiated by irradiation with active energy rays such as radiation, electron beams, ultraviolet rays, etc. In addition, irradiation with active energy rays and the polymerization initiator may be used in combination.

[0098] (polymerization form) Examples of polymerization forms applicable to one embodiment of the present invention include aqueous solution polymerization, reversed-phase suspension polymerization, spray polymerization, droplet polymerization, bulk polymerization, and precipitation polymerization. Among them, from the viewpoint of ease of polymerization control and water absorption performance of the water absorbent resin, preferably aqueous solution polymerization or reversed-phase suspension polymerization is selected, and more preferably aqueous solution polymerization is selected. Aqueous solution polymerization is described in JP-A-4-255701 and the like. Reverse-phase suspension polymerization is described in WO 2007 / 004529, WO 2012 / 023433 and the like.

[0099] Preferred forms of the continuous aqueous solution polymerization include high-temperature initiation polymerization, high-concentration polymerization, and foaming polymerization. "High-temperature initiation polymerization" refers to a polymerization form in which the temperature of the aqueous monomer solution at the start of polymerization is preferably 35°C or higher, more preferably 40°C or higher, even more preferably 45°C or higher, and particularly preferably 50°C or higher, and is preferably below the boiling point of the aqueous monomer solution. "High-concentration polymerization" refers to a polymerization form in which the monomer concentration at the start of polymerization is preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher, and is preferably below the saturated concentration of the aqueous monomer solution. "Foaming polymerization" refers to a polymerization form in which the aqueous monomer solution containing a foaming agent or bubbles is polymerized. These polymerization forms may be carried out alone, or two or more of them may be used in combination. The aqueous solution polymerization may be either a batch type or a continuous type, but a continuous type is preferred from the viewpoint of production efficiency. As a polymerization form applicable to one embodiment of the present invention, a polymerization form in which the polymerization reaction is quickly started after the addition of a polymerization initiator is preferable. As the polymerization form, for example, a polymerization form in which the polymerization reaction starts within 1 minute after adding a polymerization initiator is preferable. In addition, as the polymerization form, a polymerization form in which the polymerization reaction is also quickly completed is preferable. As the polymerization form, for example, a polymerization form in which the polymerization reaction is completed within 1 minute after the polymerization reaction starts is preferable.

[0100] Further, examples of the continuous aqueous solution polymerization include the continuous belt polymerization described in U.S. Pat. Nos. 4,893,999, 6,906,159, 7,091,253, 7,741,400, 8,519,212, and JP-A-2005-36100, and the continuous kneader polymerization described in U.S. Pat. No. 6,987,151, etc.

[0101] The method for dispersing bubbles in the foaming polymerization includes a method for dispersing a gas dissolved in a monomer aqueous solution as bubbles by reducing the solubility, a method for introducing a gas from the outside and dispersing it as bubbles, a method for adding a foaming agent to a monomer aqueous solution to foam it, etc. In addition, the above-mentioned dispersion methods may be appropriately used in combination depending on the physical properties of the target water absorbent resin.

[0102] In the case of introducing a gas from the outside, examples of the gas include oxygen, air, nitrogen, carbon dioxide, ozone, and a mixture of these gases. From the viewpoints of polymerization property and cost, an inert gas such as nitrogen or carbon dioxide is preferably used, and more preferably nitrogen is used.

[0103] Examples of the foaming agent that can be used include an azo compound, an organic or inorganic carbonate solution, a dispersion, and a powder having a particle size of 0.1 μm or more and 1000.0 μm or less. Among them, inorganic carbonates are preferable, and specifically, carbonates and hydrogen carbonates such as sodium carbonate, ammonium carbonate, and magnesium carbonate can be used.

[0104] Drying becomes easy by gel crushing the foamed hydrogel obtained by the foaming polymerization. In addition, by making the water-absorbing resin into a foamed shape, the water absorption speed of the water-absorbing resin can be improved, and furthermore, fixation to an absorbent article becomes easy. The foamed shape can be judged by confirming the pores on the surface of the water-absorbing resin with an electron microscope, for example, pores having a diameter of 1 μm or more and 100 μm or less. The number of pores is preferably 1 or more, more preferably 10 or more, and preferably 10,000 or less, more preferably 1,000 or less per particle of the water-absorbing resin, and can be controlled by adjusting the conditions in the foaming polymerization.

[0105] [3-3] Gel crushing process (step (iii)) This step is a step of crushing the hydrogel during and / or after the polymerization step to obtain a particulate hydrogel. Specifically, the hydrogel may be crushed during the polymerization step, or may be crushed after the polymerization step. That is, this step is a step of crushing the hydrogel to obtain a particulate hydrogel (hereinafter referred to as "particulate hydrogel"). In addition, this step is referred to as "gel crushing" to distinguish it from the "crushing" in the crushing step described later. In addition, the subject of gel crushing is not only the hydrogel obtained in the polymerization step, but may also include a granulated gel obtained by mixing the fine powder recovered in the classification step described later with an aqueous liquid, unless otherwise specified. The other steps are similar in purpose unless otherwise specified.

[0106] The gel crushing refers to adjusting the hydrogel to a predetermined size using a screw extruder such as a kneader or a meat chopper, or a gel crusher such as a cutter mill.

[0107] When the hydrogel is crushed, it is preferable to add hot water and / or steam to the gel crusher. By adding hot water and / or steam, a particulate hydrogel having low adhesion and good breathability is obtained, which is preferable because it is easy to dry. The temperature of the hot water is preferably 40°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher, and preferably 100°C or lower.

[0108] Regarding the embodiment and operating conditions of the gel crushing, the aqueous solution polymerization employs a method described in a document describing continuous aqueous solution polymerization. In addition, the contents described in the pamphlet of International Publication No. 2011 / 126079 are also preferably applied to one embodiment of the present invention. In addition, when the polymerization form is kneader polymerization, the polymerization step and the gel crushing step are carried out simultaneously. In addition, by passing through the gel crushing step in one embodiment of the present invention, an irregularly crushed water absorbent resin can be obtained.

[0109] In addition, the method for producing a water-absorbent resin according to one embodiment of the present invention may include a granulation step in which fine powder recovered in a classification step described later is mixed with an aqueous liquid to obtain a granulated gel, at least one step from the end of the gel crushing step to the completion of drying in a drying step, and / or a granulated gel adding step in which the granulated gel is added to the hydrogel between the steps. In addition, in the gel crushing step of the present invention, it is preferable to appropriately control the gel crushing energy. The particulate hydrogel obtained by gel crushing with the below-mentioned predetermined gel crushing energy improves the water absorption rate in terms of the physical properties of the water-absorbent resin obtained thereafter, for example, the FSR described in International Publication No. 2009 / 016055 and the Vortex described in JIS K7224 (1996) "Testing method for water absorption rate of superabsorbent resin".

[0110] Here, in one embodiment of the present invention, the "gel grinding energy" refers to the unit energy required by the gel grinding device when grinding the hydrogel, i.e., the mechanical energy per unit mass of the hydrogel, and does not include the energy for heating and cooling the jacket or the energy of the water and steam to be input. The "gel grinding energy" is abbreviated as "GGE" from the English term "Gel Grinding Energy".

[0111] When the gel grinding device is driven by three-phase AC power, the GGE is calculated by the following formula (I): GGE [J / g] = {√3 × voltage × current × power factor × motor efficiency} / {Mass of hydrogel fed into the gel grinder per second}...Equation (I) The "power factor" and "motor efficiency" are values ​​specific to the device that change depending on the operating conditions of the gel grinding device, and take values ​​between 0 and 1. These values ​​can be obtained by inquiring to the device manufacturer, etc. In addition, when the gel grinding device is driven by single-phase AC power, GGE can be calculated by changing "√3" in the above formula (I) to "1." The unit of voltage is [V], the unit of current is [A], and the unit of hydrous gel mass is [g / s].

[0112] The "power factor" and "motor efficiency" in the GGE are values ​​during gel crushing. The power factor and motor efficiency during idle operation are approximately defined as in the above formula (I) since the current value during idle operation is small. In the above formula (I), the "mass of hydrogel fed into the gel crusher per second" [g / s] refers to a value converted to [g / s] when the hydrogel is continuously fed by a fixed-volume feeder, for example. However, the hydrogel may contain recycled granulated gel, as described below.

[0113] In one embodiment of the present invention, the gel-grinding energy (GGE) for grinding the gel is preferably 100 J / g or less, more preferably 80 J / g or less, and even more preferably 60 J / g or less, and is preferably 20 J / g or more, more preferably 25 J / g or more, and even more preferably 30 J / g or more. By controlling the gel-grinding energy within the above range, the gel can be ground while applying an appropriate shear and compression force to the hydrogel.

[0114] In addition, when gel grinding is performed using multiple devices, such as using a screw extruder after kneader polymerization or using multiple screw extruders, the total energy consumed by each device is defined as the gel grinding energy (GGE).

[0115] In addition, when the gel crushing energy is controlled as described above, a more excellent effect can be obtained by combining the addition of hot water at the above temperature. Furthermore, gel crushing based on the above gel crushing energy may be performed after normal gel crushing.

[0116] The particle size of the particulate hydrogel pulverized by the gel crushing step is preferably in the range of 0.1 mm or more and 10 mm or less from the viewpoint of ease of drying and the physical properties of the obtained water-absorbent resin. The mass average particle size (D50) of the particulate hydrogel is preferably 0.1 mm to 5.0 mm, more preferably 0.1 mm to 2.0 mm. When the mass average particle size (D50) of the particulate hydrogel is in the above range, drying is performed sufficiently. In one embodiment of the present invention, the mass average particle size of the hydrogel subjected to the drying step is preferably in the above range, more preferably satisfying both the particle size and the mass average particle size.

[0117] The particle size of the particulate hydrogel is preferably 0.2 to 1.5, more preferably 0.2 to 1.3, and even more preferably 0.2 to 1.2. The logarithmic standard deviation (σζ) of the particle size distribution indicates the narrowness of the particle size distribution, and the smaller the value, the more uniform the particle size becomes, and the more uniform the drying can be. However, in order to make the logarithmic standard deviation (σζ) of the particle size distribution less than 0.2, a special operation such as classification of the particulate hydrogel after gel crushing is required, which is practically difficult to carry out from the viewpoint of productivity and cost. The mass average particle size (D50) and logarithmic standard deviation (σζ) of the particulate hydrogel are measured, for example, by the method described in WO2021 / 140905.

[0118] For uniform and efficient drying, the water content of the particulate hydrogel is preferably 30% by mass or more, more preferably 45% by mass or more, and is preferably 70% by mass or less, more preferably 55% by mass or less.

[0119] [3-4] Drying process (process (iv)) This step is a step of drying the gel-pulverized hydrogel to obtain a dried polymer. Specifically, this step is a step of drying the particulate hydrogel, or when a granulated gel is added, both the granulated gel and the particulate hydrogel to a desired solid content to obtain a dried polymer. The solid content, i.e., the value obtained by subtracting the water content from 100% by mass of the gel, is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, particularly preferably 92% by mass or more, and is preferably 99% by mass or less, even more preferably 98% by mass or less, particularly preferably 97% by mass or less. By setting the solid content of the dried polymer within the above range, pulverization, classification, and surface crosslinking can be efficiently performed. In this specification, "drying is completed" refers to a state in which the solid content reaches 80% by mass. Incidentally, in this step, the dried polymer is in a block shape, and the water content may differ between the upper and lower parts, the center, and the ends of the block. In this case, the dried polymer is appropriately taken from various positions, crushed if necessary, and the moisture content is measured and averaged.

[0120] In this specification, a dried polymer below the predetermined solid content may be referred to as an undried material. In addition, the "material to be dried" or "particulate hydrogel" in the drying process may include both particulate hydrogel and granulated gel. The drying process of the present invention is more effective when both particulate hydrogel and granulated gel are included. Similarly, in other processes, the hydrogel and its processed product may include granulated gel and its processed product.

[0121] Examples of the drying method in the drying step include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, stirring drying, etc. Among them, stirring drying or hot air drying is preferred from the viewpoint of drying efficiency. Stirring drying is preferably performed with a stirring dryer such as a paddle dryer or a rotary drum dryer. In addition, hot air drying is preferably performed with a ventilation band type dryer that performs hot air drying on a ventilation belt. By using a ventilation band type dryer, efficient drying can be performed while preventing physical damage to the dried material such as a dried polymer or a particulate hydrous gel during drying, generation of fine powder due to friction, etc.

[0122] In the case of drying with hot air, the drying temperature, i.e., the temperature of the hot air, is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and is preferably 250° C. or lower, more preferably 230° C. or lower, and even more preferably 200° C. or lower, in consideration of drying efficiency. The drying time is preferably 10 minutes to 120 minutes, more preferably 20 minutes to 90 minutes, and even more preferably 30 minutes to 60 minutes. By setting the drying temperature and drying time within the ranges, the physical properties of the obtained water absorbent resin can be within the desired range. Other drying conditions may be appropriately set depending on the moisture content, total mass, and target solid content of the particulate hydrous gel or granulated gel to be dried. When band drying is performed, the conditions described in WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, etc. may be appropriately applied.

[0123] [3-5] Grinding process, classification process (process (v)) The pulverization step is a step of pulverizing the dried polymer, and the classification step is a step of removing fine powder from the pulverized dried polymer. Specifically, the dried polymer obtained through the drying step is pulverized in the pulverization step, and adjusted to a desired particle size range in the classification step to obtain a water-absorbent resin. By passing through the pulverization step after drying, an irregularly pulverized water-absorbent resin can be obtained.

[0124] Examples of the grinding device used in the grinding step include high-speed rotary grinders such as roll mills, hammer mills, screw mills, and pin mills, as well as vibration mills, knuckle-type grinders, and cylindrical mixers. Among these, from the viewpoint of grinding efficiency, a roll mill is preferably selected. Moreover, a plurality of these grinders can be used in combination.

[0125] The particle size adjustment method in the classification step includes sieve classification using a JIS standard sieve (JIS Z 8801-1 (2000)) and air flow classification. Among them, sieve classification is preferably selected from the viewpoint of classification efficiency. Note that, from the viewpoint of ease of pulverization, a classification step may be additionally performed before the pulverization step.

[0126] The particle size distribution of the water absorbent resin is preferably such that the mass median particle diameter (D50) is 300 μm or more and 600 μm or less, and the ratio of particles less than 150 μm is 5 mass% or less. The upper limit of the mass median particle diameter (D50) is more preferably 500 μm or less, and even more preferably 450 μm or less. The ratio of particles less than 150 μm is more preferably 4 mass% or less, even more preferably 3 mass% or less, and particularly preferably 2 mass% or less. The logarithmic standard deviation (σζ), which indicates the narrowness of the particle size distribution, is preferably 0.20 or more, more preferably 0.25 or more, even more preferably 0.27 or more, and is preferably 0.50 or less, more preferably 0.45 or less, even more preferably 0.43 or less, particularly preferably 0.40 or less, and most preferably 0.35 or less. The logarithmic standard deviation (σζ) of the particle size distribution indicates the narrowness of the particle size distribution, and the smaller the value, the more uniform the particle diameter becomes, and there is an advantage that the segregation of the particles is reduced. Preferably, the mass median particle size (D50) and the proportion of particles less than 150 μm are satisfied, and more preferably, the mass median particle size (D50), the proportion of particles less than 150 μm, and the logarithmic standard deviation are satisfied, and these can be appropriately combined within the above-mentioned ranges.

[0127] The mass-average particle diameter (D50) and the logarithmic standard deviation (σζ) can be measured by the measurement method described in “(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution” in U.S. Pat. No. 7,638,570.

[0128] The above-mentioned particle size is also applied to the water absorbent resin after the pulverization step and the classification step. Therefore, when surface crosslinking is performed, it is preferable to perform surface crosslinking treatment in the surface crosslinking step so as to maintain the particle size in the above range adjusted in the water absorbent resin before surface crosslinking, and it is more preferable to provide a sizing step after the surface crosslinking step to adjust the particle size. Therefore, it is preferable that the water absorbent resin produced by the production method according to one embodiment of the present invention also satisfies that the mass average particle diameter (D50) and the ratio of particles less than 150 μm are within the above range, and it is more preferable that the mass average particle diameter (D50), the ratio of particles less than 150 μm, and the logarithmic standard deviation (σζ) of the particle size distribution are within the above range. More preferably, the water absorbent resin produced by the production method according to one embodiment of the present invention has a mass average particle diameter (D50) of 300 to 600 μm, a ratio of particles less than 150 μm is 5 mass% or less, and a logarithmic standard deviation (σζ) of the particle size distribution is 0.20 to 0.50.

[0129] [3-6] Surface crosslinking step (step (vi)) This step is a step of providing a portion with a higher crosslink density on the surface layer of the water absorbent resin before surface crosslinking obtained through each step described above, and is configured to include a mixing step, a heat treatment step, a cooling step, etc. In the surface crosslinking step, radical crosslinking, surface polymerization, a crosslinking reaction with a surface crosslinking agent, etc. occur on the surface of the water absorbent resin before surface crosslinking, and a surface crosslinked water absorbent resin is obtained.

[0130] The maximum temperature (powder temperature) of the water absorbent resin during the surface cross-linking step, that is, the maximum temperature (powder temperature) of the water absorbent resin during the heat treatment step, is preferably 180°C or higher, more preferably 190°C or higher.

[0131] [3-6-1] Mixing process This step is a step of obtaining a mixture by mixing a solution containing a surface cross-linking agent (hereinafter, referred to as a "surface cross-linking agent solution") with a water absorbent resin before surface cross-linking in a mixer.

[0132] (Surface cross-linking agent) In one embodiment of the present invention, a surface cross-linking agent is used during the surface cross-linking. The surface cross-linking agent is as described above in [Polyacrylic acid (salt)-based water-absorbing resin].

[0133] The amount of the surface crosslinking agent used, or the total amount when multiple types are used, is preferably 0.01 to 10.00 parts by mass, more preferably 0.01 to 5.00 parts by mass, and even more preferably 0.01 to 2.00 parts by mass, relative to 100 parts by mass of the crosslinked polymer. By setting the amount of the surface crosslinking agent used within this range, an optimal crosslinked structure can be formed in the surface layer of the crosslinked polymer, and a water absorbent resin with high physical properties can be obtained.

[0134] The surface cross-linking agent is preferably added as an aqueous solution to the water absorbent resin before surface cross-linking. In this case, the amount of water used is preferably 0.1 to 20.0 parts by mass, more preferably 0.3 to 15.0 parts by mass, and even more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water absorbent resin before surface cross-linking. By setting the amount of water used within the range, the handleability of the surface cross-linking agent solution is improved, and the surface cross-linking agent can be evenly mixed with the water absorbent resin before surface cross-linking.

[0135] In addition, the hydrophilic organic solvent may be used together with the water as necessary to prepare the surface crosslinking agent solution. In this case, the amount of the hydrophilic organic solvent used is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the water absorbent resin before surface crosslinking. Specific examples of the hydrophilic organic solvent include lower alcohols such as methyl alcohol; ketones such as acetone; ethers such as dioxane; amides such as N,N-dimethylformamide; sulfoxides such as dimethyl sulfoxide; and polyhydric alcohols such as ethylene glycol. However, it is preferable to limit the use of these hydrophilic organic solvents to as small an amount as possible.

[0136] In addition, various additives can be added to the surface cross-linking agent solution in an amount of 5 parts by mass or less, or can be added separately in the mixing step.

[0137] (Mixing method, mixing conditions) The water absorbent resin and the surface crosslinking agent solution are mixed by a method in which a surface crosslinking agent solution is prepared in advance, and the solution is preferably sprayed or dropped, more preferably sprayed, onto the crosslinked polymer to mix.

[0138] The mixing device for carrying out the mixing preferably has a torque required for uniformly and reliably mixing the water absorbent resin and the surface crosslinking agent. The mixing device is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer. The rotation speed of the high-speed stirring type mixer is preferably 100 rpm or more, more preferably 300 rpm or more, and is preferably 10000 rpm or less, more preferably 2000 rpm or less.

[0139] The temperature of the water absorbent resin to be supplied in this step is preferably 35° C. to 80° C., more preferably 35° C. to 70° C., and further preferably 35° C. to 60° C., from the viewpoint of mixability with the surface crosslinking agent solution and coagulation property of the humidified mixture. The mixing time is preferably 1 second or more, more preferably 5 seconds or more, and preferably 1 hour or less, more preferably 10 minutes or less.

[0140] [3-6-2] Heat treatment process This step is a step of applying heat to the mixture obtained in the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin. The heat treatment of the water-absorbent resin may be performed by heating the water-absorbent resin in a stationary state or in a fluidized state using a power such as stirring, but heating under stirring is preferable in that the entire humidified mixture can be heated evenly. From the above viewpoint, examples of the heat treatment device include a paddle dryer, a multi-fin processor, and a tower dryer.

[0141] The so-called controlled temperature of the heat treatment device is sufficient if it can heat the water absorbent resin to a temperature described later, and does not need to be constant from the beginning to the end of the process. However, in order to prevent partial overheating, the temperature is preferably 50°C to 300°C. When emphasis is placed on damage resistance as a physical property of the obtained water absorbent resin, the temperature is more preferably 250°C or lower, further preferably 70°C to 230°C, and even more preferably 90°C to 220°C.

[0142] On the other hand, when importance is attached to water absorption performance, the temperature is more preferably 120°C to 280°C, further preferably 150°C to 250°C, and particularly preferably 170°C to 230°C.

[0143] The heating time is preferably 1 to 180 minutes, more preferably 5 to 120 minutes, even more preferably 10 to 120 minutes, and even more preferably 15 to 60 minutes. If the heating time is shorter than 1 minute, the surface cross-linking treatment is insufficient, and the absorbency against pressure (AAP) is reduced. On the other hand, if the heating time is longer, coloring occurs or the absorbency against no pressure (CRC) is reduced too much.

[0144] [3-6-3] Cooling process This step is an optional step that is provided as necessary after the heat treatment step and / or the drying step. This step is a step of forcibly cooling the high-temperature water absorbent resin that has been subjected to the heat treatment step to a predetermined temperature, and quickly completing the surface cross-linking reaction.

[0145] The water-absorbent resin may be cooled in a stationary state or in a flowing state using a power such as stirring, but it is preferable to cool the water-absorbent resin under stirring in order to uniformly cool the entire water-absorbent resin. From the above viewpoint, examples of the cooling device for cooling include a paddle dryer, a multi-fin processor, and a tower dryer. These cooling devices can also be of the same specifications as the heat treatment device used in the heat treatment step. This is because the heat medium of the heat treatment device can be changed to a refrigerant and used as a cooling device.

[0146] The cooling temperature in this step may be appropriately set depending on the heating temperature in the heat treatment step, the water absorption performance of the water absorbent resin, etc., and is preferably 40°C to 100°C, more preferably 50°C to 90°C, and even more preferably 50°C to 70°C.

[0147] The present invention may include the following inventions [1] to [8]. [1] A particulate poly(meth)acrylic acid (salt)-based water-absorbing resin, The water-absorbent resin contains a water-soluble polyalkylene glycol having a weight-average molecular weight of 2000 or less, is substantially free of a liquid-permeability improver containing a polyvalent metal salt and / or water-insoluble inorganic particles, and satisfies the following (1) to (5): (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less (2) Absorption capacity under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (× 10 -7 cm 3 ·sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g s) or more (5) Initial water absorption rate under pressure (T20) is 145 seconds or less [2] The water-absorbent resin according to [1], wherein the polyalkylene glycol has a weight-average molecular weight of 200 or more. [3] The water-absorbent resin according to [1] or [2], wherein the content of the polyalkylene glycol in the entire water-absorbent resin is 0.01% by mass to 1% by mass. [4] The water-absorbing resin according to any one of [1] to [3], wherein the water-absorbing resin is an irregularly pulverized surface-crosslinked water-absorbing resin. [5] The water-absorbing resin according to any one of [1] to [4], wherein the water-absorbing resin has an initial water-absorbing speed under pressure (T5) of 25 seconds or less. [6] The water-absorbent resin according to any one of [1] to [5], wherein the total of T5, T10 and T15, which are the initial water-absorption speeds under pressure, is 160 seconds or less. [7] The water-absorbing resin according to any one of [1] to [6], wherein the water-absorbing resin has a moisture content of 5 mass % or less. [8] (i) preparing an aqueous solution of a (meth)acrylic acid (salt)-based monomer; (ii) polymerizing the aqueous (meth)acrylic acid (salt) monomer solution; (iii) a step of gel-pulverizing the hydrogel crosslinked polymer produced during or after the polymerization to obtain a particulate hydrogel; (iv) drying the particulate hydrogel to obtain a dry polymer; (v) pulverizing and / or classifying the dried polymer to obtain a particulate water absorbent resin; (vi) surface cross-linking the particulate water absorbent resin; A method for producing a particulate poly(meth)acrylic acid (salt)-based water absorbent resin, comprising: A method for producing a water-absorbing resin, comprising adding, in a step prior to the step (iii), 0.01 mass % to 1 mass % of a water-soluble polyalkylene glycol having a weight average molecular weight of 2000 or less, based on a total mass of a monomer contained in the aqueous monomer solution, without substantially adding a liquid permeability improver containing a polyvalent metal salt and / or a water-insoluble inorganic particle in all steps, and the obtained water-absorbing resin satisfies the following (1) to (5): (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less (2) Absorption capacity under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (× 10 -7 cm 3 ·sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g s) or more (5) Initial water absorption rate under pressure (T20) is 145 seconds or less EXAMPLES

[0148] The present invention will be described below with reference to examples and comparative examples, but the present invention should not be construed as being limited by these examples, etc. The physical properties described in the claims and examples of the present invention were calculated under conditions of room temperature (23±2°C) and humidity of 50±10 RH%.

[0149] [Measurement and evaluation of physical properties of water-absorbent resin] The physical properties and the like of the water-absorbent resins obtained in the following Examples and Comparative Examples were measured and evaluated by the following methods.

[0150] (Crystal Resorption Capacity (CRC)) The CRC of the water-absorbent resin was measured in accordance with NWSP 241.0.R2(15). Specifically, 0.2 g of the water-absorbent resin was placed in a nonwoven bag, and then immersed in a large excess of 0.9% by mass sodium chloride aqueous solution for 30 minutes to allow the water-absorbent resin to freely swell, and then dehydrated for 3 minutes using a centrifuge (250G), after which the absorbency under no load (CRC) (unit: g / g) was measured.

[0151] (Absorption Capacity Under Pressure (AAP)) The AAP of the water-absorbent resin was measured in accordance with NWSP 242.0.R2(15). However, in the present invention, the pressure condition was 4.83 kPa (49 g / cm 2 Specifically, a large excess of 0.9 mass% sodium chloride aqueous solution was used, and 0.9 g of the water-absorbent resin was subjected to 4.83 kPa (49 g / cm 2 After swelling under a pressure of 0.7 psi (0.01 psi, 0.7 psi), the AAP (absorbency against pressure) (unit: g / g) was measured. That is, in this specification, the AAP (absorbency against pressure) is a value measured under a pressure of 4.83 kPa.

[0152] (Water absorption capacity of hydrous gel-like cross-linked polymer without pressure: Gel CRC) The same operation as for the CRC of the water-absorbent resin was carried out except that 0.6 g of the hydrogel cross-linked polymer was used as a sample and the free swelling time was set to 24 hours. In addition, the resin solid content of the hydrogel cross-linked polymer was measured separately using the method described below, the weight of the water-absorbent resin in the above 0.6 g of the hydrogel cross-linked polymer was obtained, and the gel CRC was calculated according to the following formula (2). Note that five measurements were made for each sample, and the average value was used. Gel CRC (g / g) = [{(mwi-mb) / msi}-1] × (100 / Wn) Equation (2) Here, msi: Weight of the hydrogel crosslinked polymer before measurement (g) mb: Weight of blank (nonwoven fabric only) after free swelling and draining (g) mwi: total weight (g) of the hydrogel crosslinked polymer and nonwoven fabric after free swelling and draining Wn: Solid content of the hydrogel crosslinked polymer (wt%) It is.

[0153] (Resin solid content of hydrous gel-like cross-linked polymer) The weight of an aluminum cup with a bottom size of about 50 mm in diameter was measured in advance and designated Wa (g). 1.00 (g) of the hydrogel crosslinked polymer was weighed into the aluminum cup, and the total weight Wb (g) of the hydrogel crosslinked polymer and the aluminum cup was measured. Then, the aluminum cup containing the water-absorbent resin was left to stand in an oven at an atmospheric temperature of 180°C for 3 hours to dry. After 3 hours, the water-absorbent resin and the aluminum cup were removed from the oven and cooled to room temperature in a desiccator. Then, the total weight Wc (g) of the water-absorbent resin and the aluminum cup after drying was measured. Using Wa, Wb, and Wc, the resin solid content of the hydrogel crosslinked polymer was calculated according to the following formula (3). Resin solid content of hydrous gel crosslinked polymer (wt%)={(Wc-Wa) / (Wb-Wa))×100 Equation (3) (Saline Flow Conductivity (SFC)) Saline flow conductivity (SFC) of water-absorbent resin (unit: x 10 -7 cm 3 ·sec / g) was measured in accordance with the measurement method described in U.S. Pat. No. 5,669,894.

[0154] Specifically, 1,500 g of the water-absorbent resin was uniformly placed in a container, and then the water-absorbent resin was immersed in artificial urine and swelled under a pressure of 2.07 kPa. The artificial urine was prepared by mixing 0.25 g of calcium chloride dihydrate, 2.0 g of potassium chloride, 0.50 g of magnesium chloride hexahydrate, 2.0 g of sodium sulfate, 0.85 g of ammonium dihydrogen phosphate, 0.15 g of diammonium hydrogen phosphate, and 994.25 g of pure water.

[0155] After 60 minutes had elapsed since the pressure was applied, the height (cm) of the gel layer, which was the swollen water-absorbent resin, was recorded. Next, 0.69% by mass saline was passed through the gel layer while the gel layer was pressurized at a pressure of 2.07 kPa. The room temperature at this time was adjusted to 20 to 25°C. Then, the amount of saline passing through the gel layer was recorded at 20-second intervals using a balance and a computer, and the flow rate Fs (T) of the passing saline was measured. The flow rate Fs (T) is measured by dividing the mass (g) of the passing saline, which increases every 20 seconds, by the passing time (s). The time when the hydrostatic pressure of the saline became constant and a stable flow rate was obtained was set as Ts, and the flow rate Fs (T = 0) was calculated using data measured for 10 minutes starting from this Ts. That is, Fs (T) was plotted against time, and Fs (T = 0) was calculated based on the results obtained by the least squares method. Fs (T=0) is the initial flow rate (g / s) of the saline solution passing through the gel layer, and the saline flow conductivity (SFC) was calculated by the following equation (4):

[0156] SFC={Fs(T=0)×L0} / (ρ×A×ΔP) Equation (4) In equation (4), L0 is the height of the gel layer (cm) and ρ is the density of the saline solution (g / cm 3 ) and A is the cross-sectional area of ​​the gel layer (cm 2 ) and ΔP is the hydrostatic pressure acting on the gel layer (dyne / cm2 ).

[0157] (Free Swell Rate (FSR)) The free swelling rate (FSR) is the rate (g / (g·s)) at which 1 g of the water-absorbent resin absorbs 20 g of a 0.9% by mass sodium chloride aqueous solution, and was measured in accordance with the measurement method described in WO 2009 / 016055.

[0158] (moisture content) 1.00 (g) of the water-absorbent resin was weighed into an aluminum cup with a bottom diameter of about 50 mm, and the total mass W1 (g) of the water-absorbent resin and the aluminum cup was measured. Then, the aluminum cup containing the water-absorbent resin was left to stand in an oven at an atmospheric temperature of 180°C for 3 hours to dry. After 3 hours, the water-absorbent resin and the aluminum cup were removed from the oven and cooled to room temperature in a desiccator. Then, the total mass W2 (g) of the water-absorbent resin and the aluminum cup after drying was measured, and the moisture content was calculated according to the following formula. Moisture content (mass%) = (W1-W2) / (mass of water-absorbent resin (g)) x 100 (T20, T5, T10, T15) T20 was measured as the time (seconds) required for 1 g of water absorbent resin to absorb 20 g of the aqueous solution prepared by dissolving 9 g of sodium chloride and 0.1 g of Lorodac (main component: linear alcohol ethoxylate having 12 to 14 carbon atoms, CAS No. 68439-50-9) in 1 L of distilled water. Specifically, it was measured according to the measurement method described in JP-A-2014-515987. Similarly, T5, T10, and T15 are the times required for absorbing 5 g, 10 g, and 15 g of the aqueous solution, respectively, and were measured according to the measurement method described in JP-A-2014-515987, as was T20.

[0159] (EFFC) EFFC is the average value of the absorbency without load (CRC) and the absorbency against load (AAP).

[0160] [Example 1] (Preparation of (meth)acrylic acid (salt) monomer aqueous solution) A 2 L polypropylene container was charged with 400 parts by mass of acrylic acid, 185 parts by mass of 48% by mass sodium hydroxide aqueous solution, 2.5 parts by mass of polyethylene glycol diacrylate (PEGDA, average number of moles of ethylene oxide added: 9), 1.3 parts by mass of 2% by mass diethylenetriaminepentaacetate trisodium aqueous solution, 373 parts by mass of deionized water, and 0.9 parts by mass of polyethylene glycol (PEG) 600 (weight average molecular weight 600, Fujifilm Wako Pure Chemical Industries, Ltd.) (0.225% by mass relative to acrylic acid) and mixed to prepare an aqueous solution (1). The aqueous solution (1) was preheated to 40°C.

[0161] Next, while stirring the heated aqueous solution (1), 185 parts by mass of 48% by mass aqueous sodium hydroxide solution was added to the aqueous solution (1) over about 30 seconds in an open-to-air state, and mixed. In this way, an aqueous monomer solution was prepared. The temperature of the aqueous monomer solution rose to about 84°C due to the heat of neutralization and heat of dissolution generated during the mixing process.

[0162] Table 1 below shows the weight average molecular weight of PEG, the amount added (% by mass relative to acrylic acid), and the amount of PEGDA added (% by mass relative to acrylic acid).

[0163] (Polymerization of (meth)acrylic acid (salt) monomers) When the temperature of the aqueous monomer solution reached 83° C., 13 parts by mass of a 5% by mass aqueous solution of sodium persulfate was added as a polymerization initiator, and the mixture was stirred for about 5 seconds to obtain a reaction liquid (1).

[0164] Next, the reaction liquid (1) was poured into a stainless steel bat-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface: Teflon (registered trademark) attached) in an open-to-air state. The bat-shaped container had been preheated using a hot plate so that the surface temperature was 40° C.

[0165] After the reaction liquid (1) was poured into the bat-shaped container, the polymerization reaction started within 1 minute. The reaction liquid (1) expanded and foamed upward in all directions while generating steam, and then contracted to a size slightly larger than the bottom of the bat-shaped container. The polymerization reaction was completed within about 1 minute. A hydrogel-like crosslinked polymer was obtained by the polymerization reaction. A part of the hydrogel-like crosslinked polymer was divided, and a part of the divided polymer was used as a sample for measurement. The gel CRC was measured using the sample for measurement. The gel CRC value of the obtained hydrogel-like crosslinked polymer is shown in Table 1 below.

[0166] (Gel Crushing) Next, the remaining hydrogel crosslinked polymer that was not used for the measurement of gel CRC was cut into an appropriate size, and then the gel was crushed using a meat chopper (model number: "HL-G22SN", manufactured by Remacom Co., Ltd.) equipped with a die having a hole diameter of 8 mm and 33 holes to obtain a particulate hydrogel. The mass average particle diameter of the particulate hydrogel was 400 μm.

[0167] (Drying, grinding, classification) The particulate hydrogel was spread on a wire mesh of 50 mesh (mesh size: 300 μm) and dried with hot air at 180° C. for 30 minutes using a ventilated batch dryer (model: “71-S6”, manufactured by Satake Chemical Machinery Co., Ltd.) to obtain a dried polymer. Next, a pulverization step was performed in which the obtained dried polymer was pulverized using a roll mill, and the pulverized product was classified using wire meshes with mesh openings of 710 μm and 150 μm. As a result, an irregularly pulverized (particulate) crosslinked polymer powder having a particle size of 150 μm to 710 μm was obtained. The obtained crosslinked polymer powder corresponds to the water absorbent resin before surface crosslinking.

[0168] (Surface crosslinking) 100 parts by mass of the obtained crosslinked polymer powder was mixed with 4.0 parts by mass of a surface crosslinking agent aqueous solution consisting of 0.4 parts by mass of ethylene carbonate, 0.7 parts by mass of propylene glycol, and 2.9 parts by mass of deionized water by spraying. The obtained mixture was heat-treated for 40 minutes in a mixer at a heat medium temperature of 210°C, and crushed until it passed through a JIS standard sieve with an opening of 710 μm, thereby obtaining a surface-crosslinked water absorbent resin. The physical properties of the obtained water absorbent resin are shown in Table 1 below.

[0169] [Examples 2 to 7] Water absorbent resins of Examples 2 to 7 were obtained in the same manner as in Example 1, except that the weight average molecular weight and the amount of PEG added were changed as shown in Table 1. Various physical properties of the obtained water absorbent resins are shown in Table 1. In Table 1, the weight average molecular weight of PEG200 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) is 200, and the weight average molecular weight of PEG2000 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) is 2000.

[0170] [Example 8] The weight average molecular weight and the amount of addition of PEG were changed as shown in Table 1, the die with a hole diameter of 6 mm and the number of holes of 52 was used in the gel crushing step, and a surface crosslinking agent aqueous solution (3.08 parts by mass) consisting of 0.18 parts by mass of 1,6-hexanediol, 0.4 parts by mass of triethylene glycol, and 2.5 parts by mass of deionized water was used for 100 parts by mass of the crosslinked polymer powder obtained in the surface crosslinking step, except that a water absorbent resin of Example 8 was obtained in the same manner as in Example 1.

[0171] [Example 9] The weight average molecular weight and the amount of addition of PEG were changed as shown in Table 1, the die with a hole diameter of 6 mm and the number of holes of 52 was used in the gel crushing step, and a surface crosslinking agent aqueous solution (3.30 parts by mass) consisting of 0.67 parts by mass of ethylene carbonate and 2.63 parts by mass of deionized water was used in 100 parts by mass of the crosslinked polymer powder obtained in the surface crosslinking step, and the water absorbent resin of Example 9 was obtained in the same manner as in Example 1.

[0172] [Example 10] The weight average molecular weight and the amount of addition of PEG were changed as shown in Table 1, the die with a hole diameter of 6 mm and the number of holes of 52 was used in the gel crushing step, and a surface crosslinking agent aqueous solution (3.0 parts by mass) consisting of 1.0 part by mass of triethylene glycol and 2.0 parts by mass of deionized water was used in 100 parts by mass of the crosslinked polymer powder obtained in the surface crosslinking step, and the water absorbent resin of Example 10 was obtained in the same manner as in Example 1.

[0173] [Comparative Example 1] Except for not adding PEG, a water-absorbent resin of Comparative Example 1 was obtained in the same manner as in Example 1. Various physical properties of the obtained water-absorbent resin are shown in Table 1.

[0174] [Comparative Examples 2 and 3] Water absorbent resins of Comparative Examples 2 and 3 were obtained in the same manner as in Example 1, except that the amount of PEG added was changed as shown in Table 1 and the heating conditions were adjusted in the surface cross-linking step so that the SFC had a value shown in Table 1. Various physical properties of the obtained water absorbent resins are shown in Table 1.

[0175] [Comparative Example 4] Into a reaction vessel consisting of a lid equipped with a thermometer, a nitrogen gas inlet tube, and an exhaust hole, and a tray with a bottom surface of 300 mm x 220 mm and a depth of 60 mm, 170 g of acrylic acid, 1800 g of 37 mass% sodium acrylate aqueous solution, 0.99 g of polyethylene glycol diacrylate (weight average molecular weight 523), 6.688 g (0.8 mass% relative to acrylic acid) of PEG2000 (weight average molecular weight 2000, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 216 g of deionized water were charged and mixed, and the vessel was immersed in a water bath at 20° C. Nitrogen gas was introduced into this aqueous solution, and the solution was degassed for 20 minutes.

[0176] After confirming that the temperature of this solution had reached 20°C, 6.61 g of a 20% by mass aqueous solution of sodium persulfate and 6.33 g of a 0.1% by mass aqueous solution of L-ascorbic acid were added under a nitrogen gas flow atmosphere and mixed by stirring. The monomer concentration was 38% by mass.

[0177] Polymerization started after 1 minute, and the temperature of the reaction system at that time was 20°C. After the start of polymerization, the polymerization system was not stirred, and the reaction vessel was subsequently immersed in a water bath at 20°C to cool. After 17 minutes, the polymerization system reached a maximum temperature of 89°C. The temperature of the water bath was then increased to 70°C, and the polymerization reaction was carried out for 20 minutes to obtain a hydrogel-like crosslinked polymer. A portion of the hydrogel-like crosslinked polymer was divided, and one portion of the divided portion was used as a sample for measurement. The gel CRC was measured using the sample for measurement. The gel CRC value of the obtained hydrogel-like crosslinked polymer is shown in Table 1 below.

[0178] Of the obtained hydrous gel-like cross-linked polymers, the remaining hydrous gel-like cross-linked polymers that were not used for the measurement of gel CRC were cut into blocks, and the cut blocks of the hydrous gel-like cross-linked polymers were gel-pulverized using a meat chopper equipped with a 9.0 mm die aperture plate to obtain particulate hydrous gel polymers.

[0179] The obtained particulate hydrogel polymer was dried in a hot air dryer at 180°C for 30 minutes to obtain a dried polymer, which was then pulverized in a roll mill and sieved through wire meshes with openings of 850 μm and 150 μm to obtain a particulate crosslinked polymer powder. The obtained crosslinked polymer powder corresponds to the water absorbent resin before surface crosslinking.

[0180] A surface cross-linking agent solution consisting of 0.025 parts by mass of ethylene glycol diglycidyl ether, 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, and 2.0 parts by mass of deionized water was mixed with 100 parts by mass of the cross-linked polymer powder by spraying. The mixture was heat-treated at 200°C for 35 minutes to obtain a surface-cross-linked particulate water absorbent resin.

[0181] 100 parts by mass of the surface-crosslinked water-absorbent resin was mixed with 0.6 parts by mass of fumed silica (Aerosil 200, manufactured by Nippon Aerosil Co., Ltd.) to obtain a water-absorbent resin of Comparative Example 4. Various physical properties of the obtained water-absorbent resin are shown in Table 1.

[0182] [Comparative Examples 5 to 6] Water absorbent resins of Comparative Examples 5 to 6 were obtained in the same manner as in Example 1, except that the weight average molecular weight and the amount of PEG added were changed as shown in Table 1. The physical properties of the obtained water absorbent resins are shown in Table 1. In Table 1, the weight average molecular weight of PEG6000 (manufactured by Kishida Chemical Co., Ltd.) is 7300 to 9300, and the weight average molecular weight of PEG20000 (manufactured by Kishida Chemical Co., Ltd.) is 18000 to 25000.

[0183] [Table 1]

[0184] From Table 1, it can be seen that the water absorbent resins of Examples 1 to 10 containing PEG have a smaller T20 than the water absorbent resin of Comparative Example 1 containing no PEG. Compared with the water absorbent resins of Comparative Examples 2 and 3 containing PEG but with a low SFC, the water absorbent resins of Examples 1 to 10, which have the same amount of PEG but with an SFC of 15 (×10 -7 cm 3 It can be seen that the water absorbent resins of Examples 1 and 5, which have a weight average molecular weight (SFC) of 1.0 (g / (g·sec / g) or more, have a small T20. In the case of the water absorbent resins of Examples 1 to 7, CRC, AAP, EFFC, and FSR are good, SFC is 15 or more and is large, and T20, T15, T10, and T5 are reduced. It can be seen that the water absorbent resin of Comparative Example 4 has PEG with the same weight average molecular weight as the water absorbent resin of Example 7, but has an FSR of less than 0.33 (g / (g·s)) and a large T20.

[0185] From the above, the water-absorbent resin according to the present invention has good performance in terms of absorbency (CRC, AAP), water absorption rate (FSR), and liquid permeability (SFC), and also has a small T20 value, for example, and is excellent in initial water absorption rate under pressure. As a result, when used in, for example, paper diapers, urine bleeding (return) is suppressed, and the user can wear the paper diaper without feeling stuffy, and can spend the time comfortably. [Industrial Applicability]

[0186] When the water-absorbent resin according to the present invention is used in an absorbent article, bleeding (backflow) of discharged liquid is suppressed, and therefore the resin can be used in various absorbent article applications. When an absorbent article such as a disposable diaper containing the water-absorbent resin according to the present invention is used, the wearer can spend his or her time comfortably without feeling stuffy.

Claims

1. (i) preparing an aqueous solution of a (meth)acrylic acid (salt)-based monomer; (ii) polymerizing the aqueous (meth)acrylic acid (salt) monomer solution; (iii) a step of gel-crushing the hydrogel crosslinked polymer produced during or after polymerization to obtain a particulate hydrogel; (iv) drying the particulate hydrogel to obtain a dry polymer; (v) pulverizing and / or classifying the dried polymer to obtain a particulate water absorbent resin before surface crosslinking; (vi) surface-crosslinking the particulate water absorbent resin before surface-crosslinking; A method for producing a surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin, comprising: In the step (i) and / or (ii), a water-soluble polyalkylene glycol having a weight average molecular weight of 2000 or less is added, and the total amount of the water-soluble polyalkylene glycol added in the step (i) and / or (ii) is 0.01% by mass to 1% by mass based on the total mass of the monomers contained in the aqueous monomer solution, In the step (ii), the temperature of the aqueous monomer solution at the start of polymerization is set to 35° C. or higher and the boiling point of the aqueous monomer solution or lower; The water absorption capacity without load of the hydrogel crosslinked polymer is 31 g / g or less and 20 g / g or more; A method for producing a water-absorbent resin, wherein the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water-absorbent resin obtained by the above-mentioned production method satisfies the following (1) to (4): (1) Absorption capacity without load (CRC) is 20 g / g or more and 35 g / g or less. (2) Absorbency under pressure (AAP) of 25 g / g or more at a pressure of 0.7 psi (3) Saline flow conductivity (SFC) is 15 (×10 -7 cm 3 ・sec / g) or more (4) Free swelling rate (FSR) of 0.33 g / (g·s) or more

2. The method for producing a water-absorbent resin according to claim 1, wherein the polyalkylene glycol has a weight average molecular weight of 200 or more.

3. The content ratio of the polyalkylene glycol to the entire surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is adjusted to 0.01% by mass to 1% by mass.

4. The method for producing a water absorbent resin according to any one of claims 1 to 3, wherein the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is an irregularly pulverized surface-crosslinked water absorbent resin.

5. The method for producing a water absorbent resin according to any one of claims 1 to 4, wherein the water content of the surface-crosslinked particulate poly(meth)acrylic acid (salt)-based water absorbent resin is 5 mass% or less.

6. The method for producing a water-absorbent resin according to any one of claims 1 to 5, wherein the logarithmic standard deviation (σζ) indicating the narrowness of the particle size distribution of the particulate hydrogel obtained by gel-pulverizing the hydrogel-like crosslinked polymer in the step (iii) is 0.2 to 1.5.

Citation Information

Patent Citations

  • Preparation of polyacrylic acid alkali metal salt bridged polymer

    JP1980084304A

  • Production of highly water-absorbing polymeric material having improved water absorption rate

    JP1982167307A

  • Water absorbing resin composition

    JP1983183754A

  • Method for producing hydrophilic polymer lump or powder

    JP2001342258A

  • Composition for modifying water absorbency of water-absorbing resin particle

    JP2012126778A